The Impact of Health Education using Video and Booklet Media on Knowledge of HIV/AIDS Prevention among Health Cadres: A Pre Experimental Study - Hartiningsih, Sri Nur; Timiyatun, Endar; Nuhayati, Pipin (GLOBAL HEALTH SCIENCE GROUP, 2024)
HIV/AIDS is still a major global health problem, in 2023 it is estimated that 42.3 million people will die with HIV/AIDS. Contagion is ongoing in all countries. It is estimated that there are 39.9 million people living with HIV. Currently there is no medicine to kill the HIV virus, but we must strive for access to prevention, diagnosis, treatment and care for HIV sufferers. Prevention and control of HIV/AIDS requires cooperation between the government and the community, especially health cadres, which needs to be continued. For health education to have more effective results, it is necessary to have health education media. Objective: This research aims to determine the effect of health education using video and booklet media on cadres' knowledge in preventing HIV/AIDS. Method: The research design in this study is Pre Experiment, one group Pretest Posttest design. Health education methods with lectures, discussions and using videos and booklets. The population in this study were active health cadres in Panjatan Kulon Progo Village, totaling 26 respondents. The sampling technique uses total sampling. The instrument used is the HIV/AIDS prevention knowledge instrument. Data analysis used paired t test. Results: The results of the study showed that there was an influence of health education using video media and booklets on cadres' knowledge about HIV/AIDS prevention with an increase in knowledge score of 31.69 and a p value of 0.000. Conclusion: This research shows that health education using video and booklet media can increase cadres' knowledge about HIV/AIDS prevention.